Poria cocos oligosaccharides ameliorate dextran sodium sulfate-induced colitis mice by regulating gut microbiota dysbiosis. Issue 2 (20th December 2022) - Lan, Ke; Yang, Huabing; Zheng, Junping; Hu, Haiming; Zhu, Tianxiang; Zou, Xiaojuan; Hu, Baifei; Liu, Hongtao
Abstract : PCOs could inhibit intestinal inflammation and restore gut barrier integrity in DSS-induced colitis mice. The gut microbiota plays a key role in colitis treatment using PCOs. Abstract : Poria cocos, a widely accepted function food in China, has multiple pharmacological activities. This study aimed to investigate the therapeutic effect and molecular mechanism of Poria cocos oligosaccharides (PCOs) against dextran sodium sulfate (DSS)-induced mouse colitis. In this study, BALB/c mice were treated with 3% (w/v) DSS for seven days to establish a colitis model. The results showed that oral administration of PCOs (200 mg per kg per day) significantly reversed the changes in the physiological indices in colitis mice, including body weight, disease activity index scores (DAI), spleen index, and colon length. From the qRT-PCR assay, it was observed that PCOs suppressed the mRNA expression of pro-inflammatory cytokines, such as Tnf-α, Il-1β, and Il-6 . In addition, PCOs protected the intestinal barrier from damage by promoting the expression of mucins and tight junction proteins at both mRNA and protein levels. Upon 16S rDNA sequencing, it was observed that PCO treatment partly reversed the changes in the gut microbiota of colitis mice by selectively regulating the abundance of specific bacteria. And Odoribacter, Muribaculum, Desulfovibrio, Oscillibacter, Escherichia – Shigella, and Turicibacter might be the critical bacteria in improving colitis via PCOs. Finally, using antibiotic mixtures to destroy the intestinal bacteria, we documented that PCO fermentation broth (PCO FB) instead of PCOs prevented the occurrence of colitis in gut microbiota-depleted mice. In conclusion, PCOs showed a protective effect on colitis by reversing gut microbiota dysbiosis. Our study sheds light on the potential application of PCOs as a prebiotic for treating colitis.